Ramucirumab plus docetaxel versus placebo plus docetaxel in patients with locally advanced or metastatic urothelial carcinoma after platinum-based therapy (RANGE): overall survival and updated results of a randomised, double-blind, phase 3 trial. Issue 1 (January 2020) - Petrylak, Daniel P; de Wit, Ronald; Chi, Kim N; Drakaki, Alexandra; Sternberg, Cora N; Nishiyama, Hiroyuki; Castellano, Daniel; Hussain, Syed A; Fléchon, Aude; Bamias, Aristotelis; Yu, Evan Y; van der Heijden, Michiel S; et al.
Summary: Background: Ramucirumab—an IgG1 vascular endothelial growth factor receptor 2 antagonist—plus docetaxel was previously reported to improve progression-free survival in platinum-refractory, advanced urothelial carcinoma. Here, we report the secondary endpoint of overall survival results for the RANGE trial. Methods: We did a randomised, double-blind, phase 3 trial in patients with advanced or metastatic urothelial carcinoma who progressed during or after platinum-based chemotherapy. Patients were enrolled from 124 investigative sites (hospitals, clinics, and academic centres) in 23 countries. Previous treatment with one immune checkpoint inhibitor was permitted. Patients were randomly assigned (1:1) using an interactive web response system to receive intravenous ramucirumab 10 mg/kg or placebo 10 mg/kg volume equivalent followed by intravenous docetaxel 75 mg/m 2 (60 mg/m 2 in Korea, Taiwan, and Japan) on day 1 of a 21-day cycle. Treatment continued until disease progression, unacceptable toxicity, or other discontinuation criteria were met. Randomisation was stratified by geographical region, Eastern Cooperative Oncology Group performance status at baseline, and visceral metastasis. Progression-free survival (the primary endpoint) and overall survival (a key secondary endpoint) were assessed in the intention-to-treat population. The study is registered with ClinicalTrials.gov, NCT02426125 ; patient enrolment is complete and the last patient on treatment is being followed up for safety issues. Findings: Between July 20, 2015, and April 4, 2017, 530 patients were randomly allocated to ramucirumab plus docetaxel (n=263) or placebo plus docetaxel (n=267) and comprised the intention-to-treat population. At database lock (March 21, 2018) for the final overall survival analysis, median follow-up was 7·4 months (IQR 3·5–13·9). In our sensitivity analysis of investigator-assessed progression-free survival at the overall survival database lock, median progression-free survival remained significantly improved with ramucirumab compared with placebo (4·1 months [95% CI 3·3–4·8] vs 2·8 months [2·6–2·9]; HR 0·696 [95% CI 0·573–0·845]; p=0·0002). Median overall survival was 9·4 months (95% CI 7·9–11·4) in the ramucirumab group versus 7·9 months (7·0–9·3) in the placebo group (stratified HR 0·887 [95% CI 0·724–1·086]; p=0·25). Grade 3 or worse treatment-related treatment-emergent adverse events in 5% or more of patients and with an incidence more than 2% higher with ramucirumab than with placebo were febrile neutropenia (24 [9%] of 258 patients in the ramucirumab group vs 16 [6%] of 265 patients in the placebo group) and neutropenia (17 [7%] of 258 vs six [2%] of 265). Serious adverse events were similar between groups (112 [43%] of 258 patients in the ramucirumab group vs 107 [40%] of 265 patients in the placebo group). Adverse events related to study treatment and leading to death occurred in eight (3%) patients in the ramucirumab group versus five (2%) patients in the placebo group. Interpretation: Additional follow-up supports that ramucirumab plus docetaxel significantly improves progression-free survival, without a significant improvement in overall survival, for patients with platinum-refractory advanced urothelial carcinoma. Clinically meaningful benefit might be restricted in an unselected population. Funding: Eli Lilly and Company.